Multiaxial fatigue tests under variable strain paths and asynchronous loading and assessment of fatigue life using critical plane models. (April 2021) - Arora, Punit; Gupta, Suneel K.; Samal, M.K.; Chattopadhyay, J.
Graphical abstract: Highlights: Variable Strain Paths (VSP) and Asynchronous Strain Path (ASP) fatigue tests. VSP tests showed that saturated loop for a given strain path is history independent. ASP tests conducted under scarcely available range of frequency ratios. Three critical plane models with Miner's rule validated for fatigue life assessments. Fatemi-Socie and in-house critical plane models resulted in accurate assessments. Abstract: In the present work, axial-torsion fatigue tests were performed under two loading categories, (i) variable strain paths sequential loading and (ii) asynchronous (different loading frequencies) conditions on low C-Mn steel. Variable strain paths tests brought out that saturated cyclic stress-strain behaviour under a given strain path, is insignificantly affected by loading history. However, transient material behaviour is history dependent. Three different critical plane models, Fatemi-Socie (FS), Smith-Watson-Topper (SWT) and Arora et al. (bi-axial SWT) along with linear damage accumulation rule were used to predict fatigue life. FS and Arora et al. model resulted in accurate assessments under both loading categories.